2013
DOI: 10.1128/jb.00510-13
|View full text |Cite
|
Sign up to set email alerts
|

d -Alanine Modification of a Protease-Susceptible Outer Membrane Component by the Bordetella pertussis dra Locus Promotes Resistance to Antimicrobial Peptides and Polymorphonuclear Leukocyte-Mediated Killing

Abstract: bBordetella pertussis is the causative agent of pertussis, a highly contagious disease of the human respiratory tract. Despite very high vaccine coverage, pertussis has reemerged as a serious threat in the United States and many developing countries. Thus, it is important to pursue research to discover unknown pathogenic mechanisms of B. pertussis. We have investigated a previously uncharacterized locus in B. pertussis, the dra locus, which is homologous to the dlt operons of Grampositive bacteria. The absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…To determine the relative surface charge, overnight cultures were washed twice with HEPES buffer (20 mM, pH 7.25) and resuspended to an OD 578 of 0.1. fluorescein isothiocyanate (FITC)-poly-L-lysine (FPLL) was added to a final concentration of 5 g/ ml, and the percentage of bound FPLL was determined as described previously (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relative surface charge, overnight cultures were washed twice with HEPES buffer (20 mM, pH 7.25) and resuspended to an OD 578 of 0.1. fluorescein isothiocyanate (FITC)-poly-L-lysine (FPLL) was added to a final concentration of 5 g/ ml, and the percentage of bound FPLL was determined as described previously (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…pertussis shows a range of susceptibility to numerous CAMPs (7), and porcine beta-defensin 1 (pBD1) protects against B. pertussis infection in a newborn piglet model, demonstrating the protective capability of CAMPs against this pathogen (8). Recently, an LPS-independent mechanism in B. pertussis was also shown to increase CAMP resistance (9). B. pertussis has thus evolved at least two separate mechanisms for CAMP resistance, suggesting that this strategy plays an important role in the survival of this human-restricted pathogen.…”
mentioning
confidence: 99%
“…The activated amino acid, which is alanine in Gram-positive bacteria, has not been conclusively determined in Gram-negative bacteria. It has been suggested that it might also be alanine in B. pertussis (14). However, in V. cholerae, a group of three alm genes confers resistance to AMPs by adding glycine to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The third V. cholerae protein required to add glycine to LPS, AlmG, is also an inner-membrane protein, but it has no homology with DltB, suggesting that there is a different target or mechanism for modifying its substrate (4). A mutant with deletion of the four B. pertussis dra (dlt) genes shows an increased sensitivity to AMP, but a specific role of the individual genes has not been tested (14). The function of DltD is unknown, even in Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation